Carbon-loaded MOF derivative aerogel and preparation method thereof
Carbon-loaded MOF derivative aerogels were prepared by 'freeze-drying-vacuum immersion-vacuum carbonization' method, which solved the problems of poor performance of wave absorbing materials and poor thermal insulation performance, and achieved low-cost and high-performance wave absorbing materials preparation , suitable for mass production and high-tech applications.
Patent Information
- Application Number
- CN202411383050.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2025-01-03
AI Technical Summary
The existing wave absorbing materials have poor performance, poor thermal insulation performance, and expensive raw materials, making it difficult to mass production.
Carbon-loaded MOF derivative aerogels are prepared by the 'freeze-drying-vacuum immersion-vacuum carbonization' method. The structural stability and absorption performance are ensured through two steps of pre-carbonization and high-temperature carbonization. Cellulose is used as a low-cost matrix material to ensure the material. The uniformity and conductivity match.
It improves wave absorption and heat insulation performance, reduces raw material costs, is suitable for large-scale production, and is suitable for high-tech fields such as communications and aerospace.
Smart Images

Figure CN119236812A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of wave absorbing materials, and in particular relates to a carbon-loaded MOF derivative aerogel and a preparation method thereof. Background Art
[0002] Absorbing materials are a type of functional material that can convert incident electromagnetic wave energy into heat or other forms of energy. Researchers are committed to developing electromagnetic absorbing materials that are "thin, light, strong in absorption, and wide in bandwidth." However, the existing absorbing material preparation technology has poor performance, high raw material costs, and is not easy to mass produce.
[0003] Among many electromagnetic absorbing materials, carbon materials have attracted much attention due to their advantages such as low density, high dielectric constant, low price, simple preparation process and stable properties. Aerogel is a kind of lightweight porous material composed mostly of air with large specific surface area, high porosity, low density and low thermal conductivity. It is considered to be an ideal candidate material for an ideal microwave absorber. The rich porosity allows a large amount of air to be stored in the aerogel, which not only reduces the density of the absorber and gives the material a certain thermal insulation performance, but also optimizes the impedance matching to a certain extent. The three-dimensional interconnected structure can form an interconnected conductive network, enhance conductive loss, produce multiple reflections and scattering, and enhance the attenuation of microwave energy.
[0004] Metal-Organic Framework (MOF) compounds have attracted widespread attention due to their adjustable structure, rich pore structure and large specific surface area. They are organic-inorganic hybrid porous crystalline materials formed by self-assembly of metal ions and organic ligands. The microwave-absorbing materials derived from magnetic metal-based MOFs are conductive and magnetic, which is beneficial to impedance matching and electromagnetic wave attenuation. Iron (Fe), cobalt (Co), nickel (Ni) and their alloys all exhibit good magnetic properties, so iron-based, cobalt-based, and nickel-based MOFs have been widely studied in the field of microwave absorption. After high-temperature pyrolysis of this type of MOFs, magnetic metal nanoparticles or magnetic metal oxides can be obtained, which are used to provide magnetic loss and are good precursors for microwave-absorbing materials.
[0005] Therefore, a composite aerogel material with good thermal insulation, microwave absorption, low cost and easy mass production needs to be developed urgently. Summary of the invention
[0006] The purpose of the present invention is to provide a carbon-loaded MOF derivative aerogel and a preparation method thereof, so as to solve the problems of poor performance of absorbing materials, poor thermal insulation performance and expensive raw material costs in the prior art.
[0007] The technical solution adopted by the present invention is:
[0008] A method for preparing a carbon-supported MOF derivative aerogel comprises the following steps:
[0009] S1: Preparation of ZIF-67 with rhombic dodecahedral structure;
[0010] S2: Preparation of cellulose aerogel;
[0011] S3: Preparation of ZIF-67@cellulose composites using rhombic dodecahedral ZIF-67 and cellulose aerogel;
[0012] S4: Carbonizing the ZIF-67@cellulose composite to obtain a carbon-loaded MOF derivative aerogel.
[0013] Furthermore, the S1 includes:
[0014] S11: Weigh 2-methylimidazole, dissolve it in a solvent, and stir to mix evenly; the solvent is one of deionized water, anhydrous ethanol or methanol, the concentration of 2-methylimidazole is controlled to be 0.2-0.3 g / ml, the stirring rate is 800-1200 rpm, and the stirring time is 10-20 minutes;
[0015] S12: Weigh cobalt nitrate hexahydrate Co(NO3)·6H2O, dissolve it in a solvent, and subject the mixed solution to ultrasonic treatment to make it uniformly mixed; the solvent is one of deionized water, anhydrous ethanol or methanol, the concentration of cobalt nitrate hexahydrate is controlled to be 0.1-0.2 g / ml, and the ultrasonic treatment time is 5-15 minutes.
[0016] Furthermore, the S1 further includes:
[0017] S13: under the condition of stirring rate of 800-1200 rpm, the solution obtained in S12 is dropped into the S11 solution for mixing, and the mass ratio of Co(NO3)·6H2O to 2-methylimidazole in the mixed solution is controlled at (0.075:1)-(0.1:1);
[0018] S14: stirring the solution obtained in S13 to obtain a ZIF-67 solution; the stirring rate is 800 to 1200 rpm, and the stirring time is 3 to 9 hours;
[0019] S15: drying the ZIF-67 solution obtained in S14 to obtain ZIF-67 with a rhombic dodecahedral structure, wherein the drying temperature is 60 to 100° C. and the drying time is 6 to 10 hours.
[0020] Further, the S2 includes:
[0021] S21: weighing cellulose and mixing it with deionized water; the cellulose is any one of methyl cellulose, carboxymethyl cellulose, and sodium carboxymethyl cellulose, and the concentration of the cellulose is 0.01-0.04 g / ml;
[0022] S22: Stir the S21 solution evenly to obtain a cellulose hydrogel; the stirring rate is 1000 to 3000 rpm, and the stirring time is 1 to 3 hours.
[0023] Furthermore, the S2 further includes:
[0024] S23: freeze-drying the cellulose gel obtained in S22 to obtain cellulose aerogel; the freezing time is 6 to 24 hours, and the drying time is 12 to 36 hours.
[0025] Further, the S3 includes:
[0026] S31: dispersing the rhombic dodecahedral ZIF-67 prepared in S15 into anhydrous ethanol to obtain a ZIF-67 suspension; the mass ratio of the rhombic dodecahedral ZIF-67 to anhydrous ethanol is (1:50) to (1:20);
[0027] S32: In a vacuum environment, the cellulose aerogel prepared in S23 is immersed in a ZIF-67 suspension. After the immersion is completed, the ZIF-67@cellulose composite is taken out from the ZIF-67 suspension and vacuum dried; the immersion time is 8 to 12 minutes; the vacuum drying temperature is 80 to 100°C, and the drying time is 25 to 35 minutes.
[0028] Furthermore, the S3 also includes:
[0029] S33: Repeat S32 until the dipping times are reached, which is 3 to 5 times.
[0030] Further, the S4 includes:
[0031] S41: in a vacuum environment of a tube furnace, the ZIF-67@cellulose composite obtained in S33 is pre-carbonized; the pre-carbonization temperature is 150-250° C., and the pre-carbonization time is 1-3 hours.
[0032] Furthermore, the S4 further includes:
[0033] S42: performing a final carbonization treatment, wherein the final carbonization temperature is 700 to 900° C. and the final carbonization time is 1 to 3 hours; after the final carbonization is completed, cooling is performed to obtain a carbon-loaded MOF derivative aerogel.
[0034] Another technical solution adopted by the present invention is:
[0035] Carbon-supported MOF derivative aerogel prepared by the above method.
[0036] The beneficial effects of the present invention are
[0037] The present invention adopts a "freeze drying-vacuum impregnation-vacuum carbonization" method to prepare a carbon-loaded MOF derivative aerogel absorbing material. First, a cellulose derivative is freeze-dried to obtain an aerogel structure with a three-dimensional porous structure, and then a MOF suspension is vacuum impregnated multiple times to obtain ZIF-67@cellulose derivative aerogel. Finally, a vacuum carbonization process is used to partially carbonize the aerogel through a pre-carbonization process to ensure the stability of the structure, and then high-temperature carbonization is performed to convert the amorphous carbon part into graphite carbon, thereby forming a carbon-loaded MOF derivative aerogel absorbing material with uniformly dispersed MOF and a stable carbon skeleton.
[0038] 1. In the prior art, the metal organic framework material suspension and the cellulose aqueous solution are directly mechanically stirred and mixed. The structure of MOF is destroyed during the mechanical stirring process, resulting in the final MOF derivative no longer having a specific shape, which is not conducive to multiple reflections or scattering of electromagnetic waves by the structure near the magnetic particles, and is not conducive to the absorption of electromagnetic waves. The present invention adopts a vacuum impregnation method, which can not only ensure that the structure of MOF is not destroyed, but also ensure the uniformity of Co particles.
[0039] 2. Most of the prior art uses a single carbonization method, but this single carbonization method can easily cause the cellulose-derived carbon aerogel to curl and deform, which is not conducive to shape control, or can cause the skeleton structure of the MOF derivative to be destroyed, which is not conducive to improving the absorption performance. Therefore, the present invention uses a secondary carbonization method, that is, low-temperature pre-carbonization to maintain the morphology; and high-temperature final carbonization to convert part of the amorphous carbon into crystalline carbon, adjust the electromagnetic parameters of the aerogel, and improve the absorption performance.
[0040] 3. The raw material cost of the present invention is low and the required basic skeleton is easy to prepare, which is suitable for mass production. The existing technology mostly uses graphene as the aerogel matrix, which is expensive. As the matrix material of the wave-absorbing aerogel, because graphene has good conductivity, too high conductivity will lead to impedance mismatch with air, which is not conducive to the absorption and loss of electromagnetic waves. The cellulose in the present invention is low in price and can be easily prepared into a three-dimensional network structure through freeze-drying technology to provide a basic skeleton for the aerogel. The material obtained by carbonizing cellulose is used as the aerogel matrix material. The carbon in the obtained carbon aerogel is partially crystalline and partially amorphous, and the conductivity is not high, which is conducive to impedance matching and electromagnetic wave absorption.
[0041] 4. The present invention selects the MOF material of ZIF-67 with Co particles. The Co contained in ZIF-67 and its unique rhombic regular dodecahedron structure enable the ZIF-67 derivative to not only load Co particles to the three-dimensional network structure carbon, but also provide it with multi-interface polarization space, which is beneficial to improve the wave absorption performance of the three-dimensional network structure carbon. Therefore, ZIF-67 will not only introduce magnetic particles, but also introduce its own skeleton structure, which is beneficial to multiple scattering of electromagnetic waves.
[0042] 5. The process stability of the method of the present invention is good. The prepared carbon-loaded MOF derivative aerogel absorbing material has uniform pore structure, stable thermal insulation and absorbing properties, and can be widely used in high-tech fields such as communications, aerospace, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0044] Figure 1 This is the microscopic morphology of ZIF-67 obtained by S1 of the present invention.
[0045] Figure 2 These are microscopic morphology images of the products obtained by S2 and S3 in Example 2 of the present invention, wherein Figure a is a microscopic morphology image of the product obtained by S2 in Example 2; Figure b is a microscopic morphology image of the product obtained by S3 in Example 2 at a magnification of 500; and Figure c is a microscopic morphology image of the product obtained by S3 in Example 2 at a magnification of 2000.
[0046] Figure 3 This is the XRD spectrum of the carbon-supported MOF derivative aerogel obtained in Example 2 of the present invention.
[0047] Figure 4 This is an infrared thermal image of the carbon-supported MOF derivative aerogel obtained in Example 2 of the present invention.
[0048] Figure 5 It is a reflectivity curve diagram of the carbon-supported MOF derivative aerogel obtained in Example 2 of the present invention. DETAILED DESCRIPTION
[0049] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0050] The complete embodiment of the present invention is as follows:
[0051] S1: Preparation of ZIF-67 with rhombic dodecahedron structure. The details are as follows:
[0052] S11: Weigh 2-methylimidazole, dissolve it in a solvent, and stir to mix evenly; the solvent is one of deionized water, anhydrous ethanol or methanol, the concentration of 2-methylimidazole is controlled to be 0.2-0.3 g / ml, the stirring rate is 800-1200 rpm, and the stirring time is 10-20 minutes.
[0053] S12: Weigh cobalt nitrate hexahydrate Co(NO3)·6H2O, dissolve it in a solvent, and use an ultrasonic device to mix the mixed solution evenly; the solvent is one of deionized water, anhydrous ethanol or methanol, the concentration of cobalt nitrate hexahydrate Co(NO3)·6H2O is 0.1-0.2 g / ml, and the ultrasonic treatment time is 5-15 minutes.
[0054] S13: Under the condition of a stirring rate of 800 to 1200 rpm, the solution obtained in S12 is dropped into the S11 solution for mixing. In the mixed solution, the mass ratio of Co(NO3)·6H2O to 2-methylimidazole is controlled at (0.075:1) to (0.1:1).
[0055] S14: The solution obtained in S13 is sealed and subjected to magnetic stirring to obtain a ZIF-67 solution; the stirring rate is 800 to 1200 rpm, and the stirring rate affects the particle size of ZIF-67. The faster the stirring rate, the smaller the particle size of ZIF-67. The stirring time is 3 to 9 hours.
[0056] S15: drying the ZIF-67 solution obtained in S14 in a drying oven to obtain ZIF-67 having a rhombic dodecahedron structure, the drying temperature being 60 to 100° C., and the drying time being 6 to 10 hours.
[0057] S2: Preparation of cellulose aerogel with porous structure. The details are as follows:
[0058] S21: weigh cellulose and mix it with deionized water; the cellulose is one of methyl cellulose, carboxymethyl cellulose and sodium carboxymethyl cellulose, and the concentration of the cellulose is 0.01-0.04 g / ml.
[0059] S22: Stir the S21 solution evenly to obtain a cellulose hydrogel; the stirring rate is 1000 to 3000 rpm, and the stirring time is 1 to 3 hours.
[0060] S23: freeze-drying the cellulose gel obtained in S22 to obtain a cellulose aerogel with a porous structure; freeze-drying is performed at -55°C, the freezing time is 6 to 24 hours, and the drying time is 12 to 36 hours.
[0061] S3: Preparation of ZIF-67@cellulose composites in which ZIF-67 is uniformly attached to cellulose aerogel. The details are as follows:
[0062] S31: Disperse the ZIF-67 prepared in S1 into anhydrous ethanol, and obtain a ZIF-67 suspension by ultrasonic dispersion; the mass ratio of ZIF-67 to anhydrous ethanol is 1:50 to 1:20.
[0063] S32: Take the cellulose aerogel prepared in S2, and immerse it in S31 in a vacuum drying oven to obtain a ZIF-67 suspension. After the immersion is completed, take out the ZIF-67@cellulose complex from the ZIF-67 suspension and vacuum dry it; the vacuum pressure of the vacuum drying oven is not higher than 0.1MPa, and the immersion time is 8 to 12 minutes; the temperature of the vacuum drying oven is 80 to 100°C, the vacuum pressure is not higher than 0.1MPa, and the drying time is 25 to 35 minutes. No mechanical stirring is required for the immersion, and there is no external force caused by mechanical stirring, which can protect the morphology from being destroyed.
[0064] S33: Repeat S32 until the dipping reaches the designed number of times, which is 3 to 5 times.
[0065] S4: Preparation of carbon-supported MOF derivative aerogels with three-dimensional porous structures. The details are as follows:
[0066] S41: The ZIF-67@cellulose aerogel obtained in S3 is placed in an alumina ceramic ark and pre-carbonized in a tubular furnace; the vacuum pressure is <-0.1Pa, the heating rate is 3°C / min, the pre-carbonization temperature is 150-250°C, and the pre-carbonization time is 1-3 hours.
[0067] S42: Final carbonization treatment. After the final carbonization is completed, the carbon is cooled to room temperature in a tube furnace to obtain a carbon-supported MOF derivative aerogel with a porous structure. The vacuum pressure is <-0.1Pa, the heating rate is 2℃ / min, the final carbonization temperature is 700-900℃, and the final carbonization time is 1-3 hours.
[0068] The purpose of pre-carbonization is to treat the porous ZIF-67@cellulose aerogel at a relatively low temperature, so that part of the surface of the porous ZIF-67@cellulose aerogel is carbonized into a stable carbon skeleton, thereby increasing its structural stability, thereby ensuring the integrity of the MOF derivative@carbon aerogel structure after the final carbonization process and reducing the structural damage rate of the MOF derivative@carbon aerogel. Therefore, in order to ensure the stability of the porous structure during the carbonization of the aerogel, the pre-carbonization time and temperature need to be strictly controlled. If the pre-carbonization temperature is too high (such as above 250°C), the pre-carbonization effect of the aerogel will be poor, the small molecules will be released rapidly, and the edges of the aerogel will curl and shrink severely; while the carbonization temperature is too low (such as below 150°C), the pre-carbonization efficiency will be low, the internal small molecules cannot be completely discharged, and the expected effect cannot be achieved. The high-temperature carbonization process is to raise the temperature to 700-900°C and carbonize at a constant temperature for 1-3 hours. The increase in carbonization temperature and the presence of Co metal particles in MOF derivatives convert the amorphous carbon around the Co metal particles into layered graphite carbon. 2 -sp 3 In the hybridization mode, sp 3 The conductivity of the carbon skeleton is changed by increasing the degree of hybridization.
[0069] Example 1
[0070] S1: Preparation of ZIF-67 with a rhombic dodecahedral structure.
[0071] S11: Weigh 4 g of 2-methylimidazole and 20 mL of deionized water (0.2 g / ml), and stir at room temperature until completely dissolved. Specifically, stir at a speed of 800 rpm for 20 minutes;
[0072] S12: Weigh 0.3 g Co(NO3)·6H2O and dissolve it in 3 mL deionized water (0.1 g / ml), and ultrasonicate it in an ultrasonic cleaner for 5 min;
[0073] S13: At 800 rpm, the solution obtained in S12 was dropped into the S11 solution (Co(NO3)·6H2O:2-methylimidazole mass ratio = 0.075:1), so that the solution changed from transparent to purple;
[0074] S14: sealing the solution obtained in S13 to ensure the sealing of the reaction system, and performing magnetic stirring, specifically, stirring at a speed of 800 rpm for 9 hours, and after the stirring is completed, a ZIF-67 solution is obtained;
[0075] S15: Dry the ZIF-67 solution obtained in S14 in a drying oven at a temperature of 60° C. for 10 hours to obtain ZIF-67 having a rhombic dodecahedron structure.
[0076] S2: Preparation of methyl cellulose aerogel with porous structure:
[0077] S21: Weigh 0.01 g / ml methylcellulose and slowly add it into deionized water to prevent agglomeration and make it difficult to disperse;
[0078] S22: The solution obtained in S21 is sealed and subjected to magnetic stirring, specifically, stirred at a speed of 1000 rpm at room temperature for 3 hours, and allowed to stand after the stirring to eliminate bubbles, thereby obtaining a transparent methylcellulose hydrogel;
[0079] S23: Pour the methylcellulose gel obtained in S22 into a cylindrical plastic mold, put it into a freeze dryer, freeze it at -55°C for 6 hours to become an ice crystal state, and then vacuum dry it for 12 hours to obtain a methylcellulose aerogel with a porous structure.
[0080] S3: Preparation of ZIF-67@methylcellulose composite with ZIF-67 uniformly attached to methylcellulose aerogel:
[0081] S31: dispersing the ZIF-67 prepared in S1 into anhydrous ethanol, and performing ultrasonic dispersion to obtain a ZIF-67 suspension, wherein the mass ratio of ZIF-67 to anhydrous ethanol is 1:50;
[0082] S32: Take the methylcellulose aerogel prepared in S2, and immerse it in S31 in a vacuum drying oven to obtain a ZIF-67 suspension. The vacuum pressure of the vacuum drying oven is not higher than 0.1 MPa, and the immersion time is 8 minutes. After the immersion is completed, the ZIF-67@methylcellulose composite is taken out from the ZIF-67 suspension and vacuum dried. The vacuum pressure of the vacuum drying oven is not higher than 0.1 MPa, the drying temperature is 80°C, and the drying time is 25 minutes;
[0083] S33: Repeat S32 three times to obtain ZIF-67@methylcellulose aerogel.
[0084] S4: Preparation of carbon-supported MOF derivative aerogels with three-dimensional porous structure:
[0085] S41: First, the ZIF-67@methylcellulose aerogel is pre-carbonized to make the aerogel structure have a certain stability. Specifically, the aerogel is placed in a tubular furnace, and the temperature in the furnace is raised to 150°C at a heating rate of 1°C / min under vacuum conditions (internal pressure <-0.1Pa), and kept at 150°C for 3 hours.
[0086] S42: The pre-carbonized ZIF-67@methylcellulose aerogel with a porous structure is further subjected to high-temperature final carbonization in a tubular furnace. Specifically, the temperature is further increased from 150°C to 700°C at a heating rate of 1°C / min, and kept at 700°C for 3 hours. After the final carbonization is completed, the sample is cooled to room temperature along with the tubular furnace to obtain a carbon-supported MOF derivative aerogel with a porous structure.
[0087] Example 2
[0088] S1: Preparation of ZIF-67 with rhombic dodecahedral structure:
[0089] S11: weigh 5.5 g of 2-methylimidazole and 20 mL of anhydrous ethanol (0.275 g / ml), and stir at room temperature until completely dissolved. Specifically, stir at a speed of 1000 rpm for 15 minutes;
[0090] S12: Weigh 0.45 g Co(NO3)·6H2O and dissolve it in 3 mL anhydrous ethanol (0.15 g / ml), and ultrasonicate it in an ultrasonic cleaner for 10 min;
[0091] S13: At a speed of 1000 rpm, the solution obtained in S12 was dropped into the S11 solution (Co(NO3)·6H2O:2-methylimidazole mass ratio = 0.08:1), so that the solution changed from transparent to purple;
[0092] S14: sealing the solution obtained in S13 to ensure the sealing of the reaction system, and performing magnetic stirring, specifically, stirring at a speed of 1000 rpm for 6 hours, and after the stirring is completed, a ZIF-67 solution is obtained;
[0093] S15: Dry the ZIF-67 solution obtained in S14 in a drying oven at a temperature of 80° C. for 8 hours to obtain ZIF-67 having a rhombic dodecahedron structure.
[0094] S2: Preparation of carboxymethyl cellulose aerogel with porous structure:
[0095] S21: Weigh 0.03 g / ml carboxymethyl cellulose and slowly add it into deionized water to prevent agglomeration and make it difficult to disperse;
[0096] S22: The solution obtained in S21 is sealed and subjected to magnetic stirring, specifically, stirred at a speed of 2000 rpm at room temperature for 2 hours, and allowed to stand after the stirring to eliminate bubbles, thereby obtaining a transparent carboxymethyl cellulose hydrogel;
[0097] S23: Pour the carboxymethyl cellulose gel obtained in S22 into a cylindrical plastic mold, put it into a freeze dryer, freeze it at -55°C for 12 hours to become an ice crystal state, and then vacuum dry it for 24 hours to obtain a carboxymethyl cellulose aerogel with a porous structure.
[0098] S3: Preparation of ZIF-67@carboxymethyl cellulose composite with ZIF-67 uniformly attached to carboxymethyl cellulose aerogel:
[0099] S31: dispersing the ZIF-67 prepared in S1 into anhydrous ethanol, and performing ultrasonic dispersion to obtain a ZIF-67 suspension, wherein the mass ratio of ZIF-67 to anhydrous ethanol is 1:35;
[0100] S32: Take the carboxymethyl cellulose aerogel prepared in S2, and immerse it in S31 in a vacuum drying oven to obtain a ZIF-67 suspension. The vacuum pressure of the vacuum drying oven is not higher than 0.1 MPa, and the immersion time is 10 min. After the immersion is completed, the ZIF-67@carboxymethyl cellulose composite is taken out from the ZIF-67 suspension and vacuum dried. The vacuum pressure of the vacuum drying oven is not higher than 0.1 MPa, the drying temperature is 90°C, and the drying time is 30 min;
[0101] S33: Repeat S32 4 times to obtain ZIF-67@carboxymethyl cellulose aerogel.
[0102] S4: Preparation of carbon-supported MOF derivative aerogels with three-dimensional porous structure:
[0103] S41: First, the ZIF-67@carboxymethyl cellulose aerogel is pre-carbonized to make the aerogel structure have a certain stability. Specifically, the aerogel is placed in a tubular furnace, and the temperature in the furnace is raised to 210°C at a heating rate of 3°C / min under vacuum conditions (internal pressure <-0.1Pa), and kept at 210°C for 2 hours.
[0104] S42: The pre-carbonized ZIF-67@carboxymethyl cellulose aerogel with a porous structure is further subjected to high-temperature final carbonization in a tubular furnace. Specifically, the temperature is further increased from 210°C to 800°C at a heating rate of 2°C / min, and kept at 800°C for 2 hours. After the final carbonization is completed, the sample is cooled to room temperature in the tubular furnace to obtain a carbon-supported MOF derivative aerogel with a porous structure.
[0105] Example 3
[0106] S1: Preparation of ZIF-67 with rhombic dodecahedral structure:
[0107] S11: weigh 6 g of 2-methylimidazole and 20 mL of methanol (0.3 g / ml), and stir at room temperature until completely dissolved. Specifically, stir at a speed of 1200 rpm for 10 minutes;
[0108] S12: Weigh 0.6 g Co(NO3)·6H2O and dissolve it in 3 mL methanol (0.2 g / ml), and ultrasonicate it in an ultrasonic cleaner for 15 min;
[0109] S13: At a speed of 1200 rpm, the solution obtained in S12 was dropped into the S11 solution (Co(NO3)·6H2O:2-methylimidazole mass ratio = 0.1:1), so that the solution changed from transparent to purple;
[0110] S14: sealing the solution obtained in S13 to ensure the sealing of the reaction system, and performing magnetic stirring, specifically, stirring at a speed of 1200 rpm for 3 hours, and after the stirring is completed, a ZIF-67 solution is obtained;
[0111] S15: Dry the ZIF-67 solution obtained in S14 in a drying oven at a temperature of 100° C. for 6 hours to obtain ZIF-67 having a rhombic dodecahedron structure.
[0112] S2: Preparation of sodium carboxymethyl cellulose aerogel with porous structure:
[0113] S21: Weigh 0.04 g / ml sodium carboxymethyl cellulose and slowly add it into deionized water to prevent agglomeration and make it difficult to disperse;
[0114] S22: The solution obtained in S21 is sealed and subjected to magnetic stirring, specifically, stirred at a speed of 3000 rpm at room temperature for 1 hour, and allowed to stand after the stirring to eliminate bubbles, thereby obtaining a transparent sodium carboxymethyl cellulose hydrogel;
[0115] S23: Pour the sodium carboxymethyl cellulose gel obtained in S22 into a cylindrical plastic mold, put it into a freeze dryer, freeze it at -55°C for 24 hours to become an ice crystal state, and then vacuum dry it for 36 hours to obtain a sodium carboxymethyl cellulose aerogel with a porous structure.
[0116] S3: Preparation of ZIF-67@sodium carboxymethyl cellulose composite with ZIF-67 uniformly attached to sodium carboxymethyl cellulose aerogel:
[0117] S31: dispersing the ZIF-67 prepared in S1 into anhydrous ethanol, and performing ultrasonic dispersion to obtain a ZIF-67 suspension, wherein the mass ratio of ZIF-67 to anhydrous ethanol is 1:20;
[0118] S32: Take the sodium carboxymethyl cellulose aerogel prepared in S2, and immerse it in S31 in a vacuum drying oven to obtain a ZIF-67 suspension. The vacuum pressure of the vacuum drying oven is not higher than 0.1 MPa, and the immersion time is 12 minutes. After the immersion is completed, the ZIF-67@sodium carboxymethyl cellulose complex is taken out from the ZIF-67 suspension and vacuum dried. The vacuum pressure of the vacuum drying oven is not higher than 0.1 MPa, the drying temperature is 100°C, and the drying time is 35 minutes;
[0119] S33: Repeat S32 5 times to obtain ZIF-67@sodium carboxymethyl cellulose aerogel.
[0120] S4: Preparation of carbon-supported MOF derivative aerogels with three-dimensional porous structure:
[0121] S41: First, the ZIF-67@sodium carboxymethyl cellulose aerogel is pre-carbonized to make the aerogel structure have a certain stability. Specifically, the aerogel is placed in a tubular furnace, and the temperature in the furnace is raised to 250°C at a heating rate of 5°C / min under vacuum conditions (internal pressure <-0.1Pa), and kept at 250°C for 1 hour.
[0122] S42: The pre-carbonized ZIF-67@sodium carboxymethyl cellulose aerogel with a porous structure is further subjected to high-temperature final carbonization in a tubular furnace. Specifically, the temperature is further increased from 250°C to 900°C at a heating rate of 5°C / min, and kept at 900°C for 1 hour. After the final carbonization is completed, the sample is cooled to room temperature along with the tubular furnace to obtain a carbon-supported MOF derivative aerogel with a porous structure.
[0123] Comparative Example 1
[0124] The difference from Example 2 is:
[0125] The metal organic framework material MIL-101 was prepared in S1.
[0126] Comparative Example 2
[0127] The difference from Example 2 is:
[0128] In S21, hydroxymethyl cellulose is weighed and mixed with deionized water;
[0129] Comparative Example 3
[0130] The difference from Example 2 is:
[0131] In S32, the immersion time is 5 min;
[0132] Comparative Example 4
[0133] The difference from Example 2 is:
[0134] In S42, the final carbonization temperature is 600°C;
[0135] Comparative Example 5
[0136] The difference from Example 2 is:
[0137] No S41;
[0138] Comparative Example 6
[0139] The difference from Example 2 is:
[0140] In S41, the pre-carbonization temperature is: 120°C;
[0141] Comparative Example 7
[0142] The difference from Example 2 is:
[0143] In S41, the pre-carbonization temperature is: 280°C;
[0144] Comparative Example 8
[0145] The difference from Example 2 is:
[0146] In S41, the pre-carbonization time is: 0.5h;
[0147] Comparative Example 9
[0148] The difference from Example 2 is:
[0149] In S41, the pre-carbonization time is: 4h;
[0150] The microwave absorption performance and thermal insulation performance of each embodiment and comparative example are shown in Table 1.
[0151] Table 1 Comparison of wave absorption performance and heat insulation performance of various embodiments and comparative examples
[0152] Minimum absorption value (dB) Effective absorption bandwidth (GHz) Insulation temperature(℃) Example 1 -21.69 4.33 147 Example 2 -23.64 5.28 154 Example 3 -22.78 4.69 151 Comparative Example 1 -20.13 4.52 152 Comparative Example 2 -22.52 4.89 121 Comparative Example 3 -18.50 2.14 150 Comparative Example 4 -19.26 3.15 142 Comparative Example 5 -15.36 1.35 124 Comparative Example 6 -18.35 2.35 137 Comparative Example 7 -19.57 3.87 147 Comparative Example 8 -15.89 2.69 135 Comparative Example 9 -20.48 4.69 143
[0153] Among the embodiments, embodiment 2 has the best comprehensive performance.
[0154] The Co contained in ZIF-67 and its unique rhombic dodecahedron structure enable ZIF-67 derivatives to not only load Co particles on the three-dimensional network carbon structure, but also provide it with multi-interface polarization space, which is beneficial to improve the absorption performance of the three-dimensional network carbon structure. However, other metal organic framework materials do not have this property. Therefore, the absorption performance of Comparative Example 1 is poor, with a minimum absorption value of only -20.13dB and an effective absorption bandwidth of only 4.52GHz.
[0155] The hydroxymethyl cellulose used in Comparative Example 2 has poor water solubility and is greatly affected by temperature, which is not conducive to forming a stable aerogel matrix. Moreover, the hydroxymethyl (-CH2OH) activity in the hydroxymethyl cellulose used in Comparative Example 2 is low, and it is difficult to provide similar reactive sites, which makes it difficult to form a high-strength and stable three-dimensional network aerogel structure during crosslinking and molding, thereby affecting the thermal insulation performance of the aerogel. Therefore, the thermal insulation performance of Comparative Example 2 is poor.
[0156] The length of the immersion time can control the amount of ZIF-67 impregnation. Too little or too much will have an adverse effect on the wave absorbing performance. Too little ZIF-67 and too little Co particle content cannot play a good role in promoting the wave absorbing performance; too much ZIF-67 and too much Co particle content will lead to impedance mismatch, which is not conducive to improving the wave absorbing performance. Therefore, the wave absorbing performance of comparative example 3 is poor, the minimum absorption value is only -18.50dB, and the effective absorption bandwidth is only 2.14GHz.
[0157] The final carbonization temperature has a great influence on the degree of carbon graphitization. If the final carbonization temperature is too low, the carbon crystallinity is too low and the conductivity is too low, which is not conducive to the absorption of electromagnetic waves. If the final carbonization temperature is too high, the carbon crystallinity is too high and the conductivity is too high, which is not conducive to impedance matching and absorption of electromagnetic waves. Therefore, the wave absorption performance of comparative example 4 is poor, the minimum absorption value is only -19.26dB, and the effective absorption bandwidth is only 3.15GHz.
[0158] In Comparative Example 5, without pre-carbonization, the volatile organic matter in cellulose or ZIF-67 is rapidly decomposed, resulting in a dramatic shrinkage or collapse of the aerogel structure, forming large structural defects and uneven pores. Such a pore structure is not conducive to improving the absorption performance, because the uneven pores will reduce the multiple scattering and absorption capacity of the aerogel material to electromagnetic waves.
[0159] Comparative Example 6: Too low a pre-carbonization temperature will result in insufficient decomposition of the organic components in cellulose or ZIF-67, and the formed carbon skeleton will be relatively loose and unstable. Such a structure is prone to collapse, deformation or rupture during subsequent high-temperature final carbonization, resulting in a disordered and uneven pore structure inside the material, which is ultimately not conducive to the microwave absorption performance of the aerogel material.
[0160] In Comparative Example 7, the pre-carbonization temperature is too high, which is equivalent to the pre-carbonization process not having much effect, which will cause the volatile components in cellulose or ZIF-67 to decompose too quickly and make the carbon skeleton form too quickly, which will cause the microstructure of the aerogel to shrink, collapse, or even collapse, resulting in an incomplete or overly tight pore structure. This densified carbon skeleton will reduce the specific surface area of the aerogel material and the porosity, which is not conducive to multiple scattering and absorption of electromagnetic waves, and ultimately affect the absorbing performance.
[0161] Comparative Example 8: Too short a pre-carbonization time will affect the pore formation and distribution of the aerogel material, resulting in uneven micropore and mesoporous structures. An ideal absorbing material needs to have uniform and appropriate pores to ensure multiple scattering and absorption of electromagnetic waves. If the pre-carbonization time is insufficient, the material may have excessively large pores or closed pores, resulting in a reduction in specific surface area and impaired absorbing performance.
[0162] In Comparative Example 9, if the pre-carbonization time is too long, the aerogel material may be over-carbonized, resulting in its mechanical properties becoming brittle and the carbon skeleton becoming fragile. In the subsequent high-temperature final carbonization process, the material is prone to cracks or breaks, affecting the integrity and stability of the material structure, thereby weakening the wave absorbing performance.
[0163] In order to more clearly illustrate the embodiments of the present invention, Figure 1 This is a microscopic morphology of ZIF-67 obtained in Example 1, which shows that the embodiment of the present invention can successfully prepare ZIF-67 with a rhombic dodecahedron structure.
[0164] Figure 2 1 is a microscopic morphology diagram of the products obtained by S2 and S3 in Example 2 of the present invention, wherein Figure a is a microscopic morphology diagram of the product obtained by S2 in Example 2; Figure b is a microscopic morphology diagram of the product obtained by S3 in Example 2 at a magnification of 500; and Figure c is an enlarged view of the microscopic morphology diagram of the product obtained by S3 in Example 2 at a magnification of 2000;
[0165] As can be seen in Figure a, the sample was found to exhibit a porous structure, which was caused by the cross-linking of carboxymethyl cellulose in front of the rapidly growing ice crystals to form a three-dimensional network. After freeze-drying, a large number of micron-pore open channels were formed within the framework due to the sublimation of ice crystals. The huge internal cavity is conducive to shortening the impedance gap between the absorbent and the free space, while giving the aerogel thermal insulation properties.
[0166] As can be seen from Figure b, there are more small holes on the aerogel pore wall. These small holes can not only better improve the impedance matching of the carbon-loaded MOF derivative aerogel material, but also provide more loss paths for the incident electromagnetic waves, thereby promoting the carbon-loaded MOF derivative aerogel material's dissipation ability for electromagnetic waves.
[0167] In Figure c, it can be found that the MOF particles are evenly distributed on the pore walls of the aerogel, that is, the Co particles are evenly distributed on the aerogel, which also indicates the successful combination of MOF and aerogel.
[0168] Figure 3The XRD spectrum of the carbon-supported MOF derivative aerogel material obtained in Example 2. The porous carbon aerogel loaded with MOF has a sharp graphite (002) crystal plane diffraction peak at 26.38°, which is due to the graphitization of part of the carbon under the catalysis of Co. The graphitized carbon can improve the conductivity of the final product. At the same time, the carbon-supported MOF derivative aerogel has obvious characteristic peaks at 44.22°, 51.52° and 75.85°, which are respectively attributed to the (111), (200) and (220) crystal planes of cobalt. It shows that the present invention successfully prepared the expected Co.
[0169] Figure 4 This is an infrared thermal image of the carbon-supported MOF derivative aerogel obtained in Example 2. When the actual temperature of the heating platform rises to 304.3°C, the detected temperature of the carbon-supported MOF derivative aerogel is 150.3°C, and the thermal insulation temperature difference can reach 154°C, and there is still no expansion or contraction, indicating that the aerogel composite material can effectively inhibit heat transfer and has good thermal insulation performance.
[0170] Figure 5 This is a reflectivity curve of the MOF-loaded porous carbon aerogel absorber obtained in Example 2. It can be seen that the MOF-loaded porous carbon aerogel has excellent wave absorption performance. When the thickness is 5.4 mm, the minimum absorption peak can reach -23.64 dB, and the effective absorption bandwidth (absorption value ≤ -10 dB) can reach 5.28 GHz.
[0171] Each embodiment in this specification is described in a related manner, and the same or similar parts between the embodiments can be referred to each other, and each embodiment focuses on the differences from other embodiments. In particular, for the system embodiment, since it is basically similar to the method embodiment, the description is relatively simple, and the relevant parts can be referred to the partial description of the method embodiment.
[0172] The above description is only a preferred embodiment of the present invention and is not intended to limit the protection scope of the present invention. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention are included in the protection scope of the present invention.
Claims
1. A method for preparing carbon-supported MOF derivative aerogel, characterized in that: The following steps are involved: S1: Preparation of ZIF-67 with rhombic dodecahedral structure; S2: Preparation of cellulose aerogel; S3: Preparation of ZIF-67@cellulose composites using rhombic dodecahedral ZIF-67 and cellulose aerogel; S4: Carbonizing the ZIF-67@cellulose composite to obtain a carbon-loaded MOF derivative aerogel.
2. The method for preparing a carbon-supported MOF derivative aerogel according to claim 1, characterized in that: The S1 includes: S11: Weigh 2-methylimidazole, dissolve it in a solvent, and stir to mix evenly; the solvent is one of deionized water, anhydrous ethanol or methanol, the concentration of 2-methylimidazole is controlled to be 0.2-0.3 g / ml, the stirring rate is 800-1200 rpm, and the stirring time is 10-20 minutes; S12: Weigh cobalt nitrate hexahydrate Co(NO3)·6H2O, dissolve it in a solvent, and subject the mixed solution to ultrasonic treatment to make it uniformly mixed; the solvent is one of deionized water, anhydrous ethanol or methanol, the concentration of cobalt nitrate hexahydrate is controlled to be 0.1-0.2 g / ml, and the ultrasonic treatment time is 5-15 minutes.
3. The method for preparing a carbon-supported MOF derivative aerogel according to claim 2, characterized in that: The S1 further comprises: S13: under the condition of stirring rate of 800-1200 rpm, the solution obtained in S12 is dropped into the S11 solution for mixing, and the mass ratio of Co(NO3)·6H2O to 2-methylimidazole in the mixed solution is controlled at (0.075:1)-(0.1:1); S14: stirring the solution obtained in S13 to obtain a ZIF-67 solution; the stirring rate is 800 to 1200 rpm, and the stirring time is 3 to 9 hours; S15: drying the ZIF-67 solution obtained in S14 to obtain ZIF-67 with a rhombic dodecahedral structure, wherein the drying temperature is 60 to 100° C. and the drying time is 6 to 10 hours.
4. The method for preparing a carbon-supported MOF derivative aerogel according to claim 1, characterized in that: The S2 includes: S21: weighing cellulose and mixing it with deionized water; the cellulose is any one of methyl cellulose, carboxymethyl cellulose, and sodium carboxymethyl cellulose, and the concentration of the cellulose is 0.01-0.04 g / ml; S22: Stir the S21 solution evenly to obtain a cellulose hydrogel; the stirring rate is 1000 to 3000 rpm, and the stirring time is 1 to 3 hours.
5. The method for preparing a carbon-supported MOF derivative aerogel according to claim 4, characterized in that: The S2 further includes: S23: freeze-drying the cellulose gel obtained in S22 to obtain cellulose aerogel; the freezing time is 6 to 24 hours, and the drying time is 12 to 36 hours.
6. The method for preparing a carbon-supported MOF derivative aerogel according to claim 3 or 5, characterized in that: The S3 includes: S31: dispersing the rhombic dodecahedral ZIF-67 prepared in S15 into anhydrous ethanol to obtain a ZIF-67 suspension; the mass ratio of the rhombic dodecahedral ZIF-67 to anhydrous ethanol is (1:50) to (1:20); S32: In a vacuum environment, the cellulose aerogel prepared in S23 is immersed in a ZIF-67 suspension. After the immersion is completed, the ZIF-67@cellulose composite is taken out from the ZIF-67 suspension and vacuum dried; the immersion time is 8 to 12 minutes; the vacuum drying temperature is 80 to 100°C, and the drying time is 25 to 35 minutes.
7. The method for preparing a carbon-supported MOF derivative aerogel according to claim 6, characterized in that: The S3 further includes: S33: Repeat S32 until the dipping times are reached, which is 3 to 5 times.
8. The method for preparing a carbon-supported MOF derivative aerogel according to claim 7, characterized in that: The S4 includes: S41: in a vacuum environment of a tube furnace, the ZIF-67@cellulose composite obtained in S33 is pre-carbonized; the pre-carbonization temperature is 150-250° C., and the pre-carbonization time is 1-3 hours.
9. The method for preparing a carbon-supported MOF derivative aerogel according to claim 8, characterized in that: The S4 further comprises: S42: performing a final carbonization treatment, wherein the final carbonization temperature is 700 to 900° C. and the final carbonization time is 1 to 3 hours; after the final carbonization is completed, cooling is performed to obtain a carbon-loaded MOF derivative aerogel.
10. A carbon-supported MOF derivative aerogel prepared by the method for preparing a carbon-supported MOF derivative aerogel according to any one of claims 1 to 9.
Citation Information
Cited By
Aerogel-based porous composite material for sewage treatment as well as preparation method and application of aerogel-based porous composite material
CN120268457A
Three-dimensional oriented porous aerogel loaded with yttrium-cobalt nanoparticles as well as preparation method and application of three-dimensional oriented porous aerogel
CN121198174A
